Socio-Demographic Patterns on Child Abuse among Secondary School Students in Uganda - Ninsiima Patience; Bashaija Athanansio; Justine Momanyi Omare (Journal of Research in Education and Pedagogy, 2025)
Child abuse remains a critical global concern with millions of children experiencing physical abuse at home with most of them living with mothers who suffer emotional abuse, hence becoming a serious problem. This study sought to examine the socio-demographic patterns of child abuse among secondary school students in Uganda. The study underscored the relationship between socio-demographic characteristics and levels of abuse experienced. Using a convergent parallel research design that combined both quantitative and qualitative methods. Data were collected from 239 students and 11 school administrators through questionnaires and in-depth interviews. Quantitative data were analyzed using Adjusted Odds Ratios (AOR), Confidence Intervals (CI), and p-values, while qualitative data were analyzed thematically. The findings revealed significant socio-demographic disparities in abuse experiences and reporting patterns. Female students were more likely to report abuse (AOR = 1.4, CI: 1.0–2.1, p < 0.022), indicating gender-specific vulnerabilities, while male students tended to underreport incidents due to stigma and societal expectations. Additionally, students from certain schools reported higher rates of physical and sexual abuse (AOR = 2.1, CI: 1.2–3.8, p < 0.022), highlighting the influence of institutional factors and the urgent need for improved oversight and accountability. Qualitative findings confirmed that physical harm, sexual harassment, and emotional abuse were the most common forms of abuse. Based on these findings, the study recommends strengthening gender-sensitive interventions, auditing and reforming school policies, tailoring child protection strategies to different socio-demographic groups, simplifying reporting mechanisms to be more child-friendly, and implementing comprehensive awareness campaigns. Therefore, there should be stronger national child protection policies within the education sector are crucial for ensuring the safety and well-being of children in Uganda.